Inverse Laplace Transform by Contour Integration

The Laplace tranform of f(t), L[f(t)], is denoted as F(s) herein. Namely,
F(s) =
_

0
f(t)e
−st
dt
The basis of the inversion of a transform by contour integration is the “Mellin-Fourier” theorem:
which states that:
If
F(s) =
_

0
f(t)e
−st
dt,
then
f(t) =
1
2πi
lim
β→∞
_
α+iβ
α−iβ
F(s)e
st
ds,
where α is a constant greater than the real part of any singularity in the transform F(s).
R
i
i
α + β
α − β
α
B
A
C
D
E
F
i
r
s
t

B
r
o
m
w
i
c
h

p
a
t
h
i
i
β
− β
B
A
Q P
R
C
D
barrier
Consider the contour shown at the left of the figure, where the verticle line on α and the arc of
the circle R enaloses all singularities of F(s) on the s-plane (assuming s is a complex variable).
Usually the radius R is extended to infinty. Expressed symbolically,
lim
R→∞
_
ABCPQRDA
F(s)e
st
ds = lim
β→∞
_
α+iβ
α−iβ
F(s)e
st
ds + lim
R→∞
_
BCA
F(s)e
st
ds
. ¸¸ .
=0
+
_
PQR
F(s)e
st
ds
+ lim
R→∞
_
RDA
F(s)e
st
ds
. ¸¸ .
=0
= 2πi

j
Res
j
Usually, the last integral is zero as R → ∞ (the proof is given in textbook). So the inversion of
the Laplace transform becomes
1
f(t) =
1
2πi
_
α+i∞
α−i∞
F(s)e
st
ds
=

j
Res
j
+
1
2πi
_
RQP
F(s)e
st
ds (1)
The path of integration from α −i∞ to α + i∞ is also called the first Browmwich path, short for
Br
1
; The path of integration along the branch cut is also called the second Bromwich path, short
for Br
2
.
1 Inversion when singularities are poles
In this case, the integral in Eqn. (1) can be evaluated by the residue theorem:
f(t) =
1
2πi
_
ABCA
F(s)e
st
ds =

_
residues of F(s)e
st
_
And the residue at each pole (of different orders) can be calculated as described in previous lecture
notes.
2 Inversion when singularities are branch points
Previously, we showed that the path of a contour integration cannot cross a “barrier” erected from
a branch point. Assume now the function F(s)e
st
has a branch point at the origin and the branch
cut follows the negative real axis, then the integration follows the shown contour (ABCPQRDA)
at the right figure.
Since within the modified integration domain there is no singularity, the closed integral around
contour ABCPQRDA is zero by Cauchy’s theorem. Furthermore, as β → ∞, the arc integrals
along BCP and RDA are zero. Thus the inversion of the Laplace Transform becomes
f(t) =
1
2πi
_
α+i∞
α−i∞
F(s)e
st
ds =
1
2πi
_
RQP
F(s)e
st
ds =
1
2πi
_
Br
2
F(s)e
st
ds
2
Example 1: Evaluate the inverse transform of 1/(s

s + 1).
We evaluate the transform of the function df(t)/dt:
df(t)
dt
= L
−1
_
1

s + 1
_
and make the coordinate translation λ = s + 1, such that
df(t)
dt
=
1
2πi
_
Br2
e
(λ−1)t


λ
(2)
The integral along RQP will be divided into three parts.
(i) Integration around the circle Q of radius δ:
Let λ = δe

, where θ varies from −π to π. Thus dλ = iδe

dθ and

λ = δ
1/2
e
iθ/2
_
Q
e
(λ−1)t

λ
dλ = e
−t
_
Q
e
λt

λ
dλ = lim
δ→0
e
−t
_
π
−π
e
δ(cos θ+i sin θ)t
δ
1/2
e
iθ/2
_
iδe


_
= 0.
(ii) Integration along RQ:
Because the line RQ is below the branch cut, define λ = xe
−iπ
, with x varying from
∞ to 0.
Thus λ = x[cos(−π) +i sin(−π)] = −x, dλ = e
−iπ
dx = −dx, and

λ = x
1/2
e
−iπ/2
=
−i

x.
_
RQ
e
(λ−1)t

λ
dλ = e
−t
_
0

e
−xt
−i

x
(−dx) = ie
−t
_

0
e
−xt

x
dx.
(iii) Integration along QP:
Because the line RQ is above the branch cut, define λ = xe
+iπ
, with x varying from
0 to ∞.
Thus λ = x[cos(π)+i sin(π)] = −x, dλ = e

dx = −dx, and

λ = x
1/2
e
iπ/2
= +i

x.
_
QP
e
(λ−1)t

λ
dλ = e
−t
_

0
e
−xt
+i

x
(−dx) = ie
−t
_

0
e
−xt

x
dx.
Add all three results together and substitute into Eqn. (2) yields
df(t)
dt
=
e
−t
π
_

0
e
−xt

x
dx. (3)
3
By putting xt = α
2
so that 1/

x =

t/α and dx = (2/t)αdα yields
df(t)
dt
=
2e
−t
π

t
_

0
e
−α
2
dα =
e
−t

πt
,
_
because
2

π
_

0
e
−η
2
dη = 1
_
So
f(t) =
1

π
_

t
0
e


t
2

t
d(

t
2
) =
1

π
_

t
0
e


t
2

t
2

t d(

t) = erf(

t).
Example 2: Prove the Theorem 82 in the textbook. Namely, show that the inverse transform of
F(s) = e
−k

s
is f(t) =
k
2

πt
3
e

k
2
4t
.
There is a branch point at s = 0. Let the branch cut be [−∞, 0].
• Along the lower branch cut from −∞ to 0:
Let s = xe
−πi
= −x,

s = −i

x, ds = −dx
_
lower
=
_
0

e
+

xki
e
−xt
(−dx) =
_

0
e
+

xki
e
−xt
dx
• Along the top branch cut from 0 to ∞:
Let s = xe
+πi
= −x,

s = +i

x, ds = −dx
_
top
=
_

0
e


xki
e
−xt
(−dx) = −
_

0
e


xki
e
−xt
dx
• Along the circle around s = 0:
Let s = e

,

s =

e
iθ/2
, ds = ie


_
circle
= lim
→0
_
π
−π
e


k[cos(θ/2)+i sin(θ/2)]
e
(cos θ+i sin θ)
(ie

dθ) = 0
Thus
f(t) = L
−1
[F(s)] =
1
2πi
_

0
e
−xt
_
e

xki
−e


xki
_
dx
=
1
π
_

0
e
−xt
sin(

xk)dx
=
1
π
_√
πk
2t
3/2
e

k
2
4t
_
=
k
2

πt
3
e

k
2
4t
4
Note: It’s very difficult to evaluate the last integral in the above expression.
Example 3: Prove that
f(t) = L
−1
_
1
s
e
−a

s
_
= erfc
_
a
2

t
_
.
The integrand has a branch point at s = 0. Use the branch cut [−∞, 0] as before.
• Around the small circle at s = 0:
Let s = e

, ds = ie

dθ.
_
circle
= lim
→0
_
π
−π
1
e

e


[cos(θ/2)+i sin(θ/2)]
e
−(cos θ+i sinθ)t
(ie

dθ) = i
_
π
−π
dθ = 2πi
• Along bottom line:
Let s = xe
−πi
= −x,

s = −

xi.
_
bottom
=
_
0

1
−x
e
+a

xi
e
−xt
(−dx) = −
_

0
1
x
e
+a

xi
e
−xt
(dx)
• Top bottom line:
Let s = xe
+πi
= −x,

s =

xi.
_
top
=
_

0
1
−x
e
−a

xi
e
−xt
(−dx) =
_

0
1
x
e
−a

xi
e
−xt
(dx)
Thus
_
bottom
+
_
top
=
_

0
e
−xt
_
e
−a

xi
−e
+a

xi
_
dx
x
= −2i
_

0
e
−xt
sin
_
a

x
_
dx
x
= −4i
_

0
e
−y
2
t
sin(ay)
dy
y
(x = y
2
, y > 0) (4)
At this stage, we need to utilize a known result:
_

0
e
−y
2
α
2
cos(2βy)dy =

π

e

β
2
α
2
Integratin the above result with respect to β yields
1
2
_

0
e
−y
2
α
2 sin(2βy)
y
dy =

π

_
β
0
e

β
2
α
2

=

π
2
_
β/α
0
e
−u
2
du, (β = αu)
=
π
4
erf(β/α) (5)
5
In view of Eq. (5), Eq. (4) becomes
_
bottom
+
_
top
= −2πi · erf
_
a
2

t
_
Thus
f(t) =
1
2πi
__
circle
+
_
bottom
+
_
top
_
= 1 −erf
_
a
2

t
_
= erfc
_
a
2

t
_
.
Note: This should also be able to be proved from the result in Example 2.
3 Inversion when both poles and branch cuts exist
f(t) =
1
2πi
_
Br2
F(s)e
st
ds +

_
residues of F(s)e
st
_
Example 4: Re-evaluate the inverse transform of 1/(s

s + 1)
The point s = 0 is a simple pole of order 1, and its associate residue is
Residue at s = 0 = lim
s→0
1

s + 1
= 1.
This is because at s = 0, s + 1 = e
0i
.
The point s = −1 is a branch point, with the branch cut extending to negative infinity.
(i) Integration around the circle Q of radius δ:
Let s + 1 = δe

, where θ varies from −π to π. Thus ds = iδe

dθ and

s + 1 =
δ
1/2
e
iθ/2
_
Q
e
st
s

s + 1
ds = lim
δ→0
e
−t
_
π
−π
e
δ(cos θ+i sin θ)t
(−1 + δe


1/2
e
iθ/2
_
iδe


_
= 0.
(ii) Integration along RQ (below):
6
Because the line RQ is below the branch cut, define s + 1 = xe
−iπ
, with x varying
from ∞ to 0.
Thus s = −1 −x, ds = e
−iπ
dx = −dx, and

s + 1 = x
1/2
e
−iπ/2
= −i

x.
_
RQ
e
st
s

s + 1
ds =
_
0

e
−(1+x)t
(−1 −x)(−i

x)
(−dx) = −i
_

0
e
−(1+x)t
(1 + x)

x
dx.
(iii) Integration along QP (above):
Because the line RQ is above the branch cut, define s + 1 = xe
+iπ
, with x varying
from 0 to ∞.
Thus s = −1 −x, ds = e

dx = −dx, and

s + 1 = x
1/2
e
iπ/2
= +i

x.
_
QP
e
st
s

s + 1
ds =
_

0
e
−(1+x)t
(−1 −x)(i

x)
(−dx) = −i
_

0
e
−(1+x)t
(1 + x)

x
dx.
Add all three results together and substitute into Eqn. (2) yields
f(t) = 1 −
2i
2πi
_

0
e
−(1+x)t
(1 + x)

x
dx = 1 −
1
π
_

0
e
−(1+x)t
(1 + x)

x
dx
= 1 −
1
π
_
π
_
1 −erf(

t)
_
_
= erf(

t)
Note: It is very difficult to derive that
_

0
e
−(1+x)t
(1 + x)

x
dx = π[1 −erf(

t)].
But it will be easy to show that
df(t)
dt
=
1
π
_

0
e
−(1+x)t

x
dx =
e
−t
π
_

0
e
−xt

x
dx,
which is the same as Eq. (3).
Example 5: Evaluate the inverse Laplace transform of F(s)
F(s) =
K
0
(r
_
s/ν + 1/b
2
)
sK
0
(a
_
s/ν + 1/b
2
)
7
where a, b, and ν are real and positive numbers, the function K
0
() is a zeroth-order, modified Bessel
function of the second kind.
Solution: There is a simple pole at s = 0 and a branch point at s = −ν/b
2
.
Res(s = 0) = lim
s→0
K
0
(r
_
s/ν + 1/b
2
)
K
0
(a
_
s/ν + 1/b
2
)
e
st
=
K
0
(r/b)
K
0
(a/b)
.
This is because at s = 0, s + ν/b
2
= ν/b
2
e
0i
. Hence
_
s + ν/b
2
=

ν/b.
Take the branch cut along the negative real axis of the s-plane from s = −ν/b
2
to minus infinity,
i.e., [−∞, −ν/b
2
].
• Along the top branch cut:
Let s + ν/b
2
= νx
2
e
πi
(i.e.,
s
ν
+
1
b
2
= x
2
e
πi
) with 0 < x < ∞, so ds = −2νxdx.
_
top
= 2
_

0
K
0
(irx)e
−νt/b
2
−νtx
2
−(x
2
+ 1/b
2
)K
0
(iax)
(−xdx)
= 2e
−νt/b
2
_

0
e
−νtx
2
[J
0
(rx) −iY
0
(rx)]
(x
2
+ 1/b
2
)[J
0
(ax) −iY
0
(ax)]
xdx
upon utilizing the relation:
K
0
(irx) = −πi[J
0
(rx) −iY
0
(rx)]/2
where J
0
() and Y
0
() are zeroth-order Bessel functions of the first and second kind, respectively.
• Along the bottom branch cut:
Let s + ν/b
2
= νx
2
e
−πi
(i.e.,
s
ν
+
1
b
2
= x
2
e
−πi
) with 0 < x < ∞, so ds = −2νxdx.
_
bottom
= 2
_
0

K
0
(−irx)e
−νt/b
2
−νtx
2
−(x
2
+ 1/b
2
)K
0
(−iax)
(−xdx)
= −2e
−νt/b
2
_

0
e
−νtx
2
[J
0
(rx) + iY
0
(rx)]
(x
2
+ 1/b
2
)[J
0
(ax) + iY
0
(ax)]
xdx
Add both branch-cut integration results together,
_
top
+
_
bottom
= 2e
−νt/b
2
_

0
e
−νtx
2
x
2
+ 1/b
2
_
J
0
(rx) −iY
0
(rx)
J
0
(ax) −iY
0
(ax)

J
0
(rx) + iY
0
(rx)
J
0
(ax) + iY
0
(ax)
_
xdx
= −4ie
−νt/b
2
_

0
e
−νtx
2
x
2
+ 1/b
2
_
J
0
(ax)Y
0
(rx) −J
0
(rx)Y
0
(ax)
J
2
0
(ax) + Y
2
0
(ax)
_
xdx
8
Adding the above result (divided by 2πi) and the residue at s = 0, also letting x = η/a, yields
f(t) =
K
0
(r/b)
K
0
(a/b)

2
π
e
−νt/b
2
_

0
e
−νtη
2
/a
2
η
2
+ a
2
/b
2
_
J
0
(η)Y
0
(rη/a) −J
0
(rη/a)Y
0
(η)
J
2
0
(η) + Y
2
0
(η)
_
ηdη
Example 6: A complete problem
For diffusion in a cylindrical geometry, the governing equation is
1
ν
∂c
∂t
=

2
c
∂r
2
+
1
r
∂c
∂r

c
b
2
, a < r < ∞, t > 0
where b, and ν are real and positive numbers. This governing equation is subject to the initial and
boundary conditions:
I.C.: c(r, 0) = 0
B.C: c(a, t) = H(t), lim
r→∞
c(r, t) →0
where a(> 0) is the boundary (for example, the radius of a cylinder).
By Laplace transform of the governing equation, we have
d
2
C(r, s)
dr
2
+
1
r
dC(r, s)
dr

_
1
b
2
+
s
ν
_
C(r, s) = 0
with the B.C.s:
C(a, s) =
1
s
, lim
r→∞
C(r, s) →0
The solution of the above equation for C(r, s) is
C(r, s) = AK
0
(r
_
s/ν + 1/b
2
) + BY
0
(r
_
s/ν + 1/b
2
)
where the Y
0
() blows up at infinity and thus must be rejected because of the boundary condition
at r →∞. Apply the B.C. at r = a determines the coefficient A and hence yields
C(r, s) =
K
0
(r
_
s/ν + 1/b
2
)
sK
0
(a
_
s/ν + 1/b
2
)
.
By making an inverse Laplace transform of C(r, s) (the solution of which is given from the previous
Example), we arrive at
c(r, t) =
K
0
(r/b)
K
0
(a/b)

2
π
e
−νt/b
2
_

0
e
−νtη
2
/a
2
η
2
+ a
2
/b
2
_
J
0
(η)Y
0
(rη/a) −J
0
(rη/a)Y
0
(η)
J
2
0
(η) + Y
2
0
(η)
_
ηdη
9
Example 7: Heat Conduction in Parallel Planes (from textbook)
The heat conduction equation in Cartesian geometry is
∂T
∂t
= α

2
T
∂x
2
The I.C and B.C.s are
T(x, 0) = T
0
T(0, t) = T
0
T(L, t) = T
1
Assume that the Laplace transform of T(x, t) is
¯
T(x, s). We have
α
d
2
¯
T
dx
2
= s
¯
T −T
0
the solution of which is
¯
T = Ae


s
α
x
+ Be
+

s
α
x
+
T
0
s
.
Applying the two B.C.s yields
¯
T =
T
0
s
+
T
1
−T
0
s
sinh(
_
s
α
x)
sinh(
_
s
α
L)
Now check to see if s = 0 is a simple pole or second-order pole, or a branch point. Tayler-expand
the hyperbolic sines
1
s
sinh(
_
s
α
x)
sinh(
_
s
α
L)
=
x
Ls
+
x
6aL
_
x
2
−L
2
_
+
_
· · ·
_
s + O(s
2
) +· · ·
Thus s = 0 is a simple pole, not a branch point (and there is no branch cut). The residue at s = 0
is immediately known from the above expansion
Res(s = 0) = (T
1
−T
0
) lim
s→0
_
s
x
Ls
e
st
_
= (T
1
−T
0
)
x
L
Other poles exist at sin(iL
_
s/α) = 0,
_
s/αL = nπi, or s
n
= −α(nπ/L)
2
.
Res(s = s
n
) = lim
s→s
n
_
_
s −s
n
sinh(
_
s
α
L)
sinh(
_
s
α
x)
s
e
st
_
_
= lim
s→s
n
_
_
1
L
2

αs
cosh(
_
s
α
L)
sinh(
_
s
α
x)
s
e
st
_
_
=
2
nπi
sinh(inπx/L)
cosh(inπ)
e
−αn
2
π
2
t/L
2
=
2

(−1)
n
sin
_
nπx
L
_
e
−αn
2
π
2
t/L
2
10
Thus the complete solution is
T −T
0
T
1
−T
0
=
x
L
+

n=0
2

(−1)
n
sin
_
nπx
L
_
e
−αn
2
π
2
t/L
2
Example 8: Coupled equations: Solve the system
d
2
x
1
dt
2
= 3x
1
−4x
2
= 0
d
2
x
2
dt
2
+ x
1
+ x
2
= 0
with the ICs:
x
1
(0) = x
2
(0) = 0, dx
1
(0)/dt = 2, dx
2
(0)/dt = 0
Solutions: The use of Laplace transform gives
(s
2
−3)¯ x
1
−4 ¯ x
2
= 2
¯ x
1
+ (s
2
+ 1)¯ x
2
= 0
Then
¯ x
1
(s) =
2(s
2
+ 1)
(s
2
−1)
2
=
(s + 1)
2
+ (s −1)
2
(s
2
−1)
2
=
1
(s −1)
2
+
1
(s + 1)
2
and
¯ x
2
(s) =
−2
(s
2
−1)
2
=
1
2
_
1
s −1

1
s + 1

1
(s −1)
2

1
(s + 1)
2
_
Hence the inversion yields
x
1
(t) = t(e
t
+ e
−t
)
and
x
2
(t) =
1
2
(e
t
−e
−t
+ te
t
−te
−t
)
11